Visual Media Center : Columbia University, Department of Art History and Archaeology (2012)
[Dt.:] Das Visual Media Center der Colombia University bietet online Bildmaterial zu verschiedenen thematischen Schwerpunkten an, vorrangig Architektur. Das Ziel ist es die Interpretationsweisen von Gemälden, Architektur und Objekten zu erkennen und zu erweitern. In der Liste der zahlreichen Projekte sind alle Themen auf einen Blick zu erfassen. - [Engl.:] The Visual Media Center explores material culture, vision, media, and pedagogy in the broadest sense to connect faculty research and student learning through the creative application of technology. The goal is to examine and extend the ways of interpreting images, objects, buildings, and sites and to reinforce Columbia s historic strengths in core education for undergraduate students, graduate student training, and faculty research. In the list of projects you can find all the topics of the Visual Media Center.